Kepanduan dalam Pembelajaran Alam : Membangun Keterampilan Hidup Melalui Pengalaman Langsung - Rifky Arfinsyah; Muhammad Riski Anugrah Pratama; Ririn Aryuni M Lapi; Maria Ika Suryani Meti; Ilmi Amalia Rahma; Kostadia Nona Lence; Maria Ermilinda Dua Lering (Jurnal Ilmiah Dan Karya Mahasiswa, 2025)
This study aims to explore the impact of nature-based learning on students' life skills. The introduction explains that direct interaction with the natural environment can enhance social, emotional, and critical thinking skills. The research method employed is a qualitative approach, with data collection through observations, interviews, and questionnaires administered to students and educators in several schools. The analysis results indicate that students engaged in nature-based learning activities show significant improvements in interpersonal skills and environmental awareness. The discussion highlights the challenges faced in implementing these programs, such as resource and time limitations, and provides suggestions for better integration into the educational curriculum. This research emphasizes the importance of nature-based learning as an effective method in modern education.